2015
DOI: 10.7554/elife.05068
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome mis-segregation and cytokinesis failure in trisomic human cells

Abstract: Cancer cells display aneuploid karyotypes and typically mis-segregate chromosomes at high rates, a phenotype referred to as chromosomal instability (CIN). To test the effects of aneuploidy on chromosome segregation and other mitotic phenotypes we used the colorectal cancer cell line DLD1 (2n = 46) and two variants with trisomy 7 or 13 (DLD1+7 and DLD1+13), as well as euploid and trisomy 13 amniocytes (AF and AF+13). We found that trisomic cells displayed higher rates of chromosome mis-segregation compared to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
21
16
9
5

Citation Types

5
92
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
79
32
25
16

Relationship

7
88

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 74 publications
(125 reference statements)
5
92
0
Order By: Relevance
“…Similarly, aneuploid clones within human colorectal cancer cultures show a selective advantage and an increase in tumorigenic behaviour under stress conditions [20]. It has also been suggested that aneuploidy in a triploid or tetraploid cell can lead to further chromosomal instability, thereby promoting tumour evolution and tumorigenesis [30,31]. This process might well directly start after tetraploidization as the molecular machinery of tetraploid cells already displays molecular signatures that prepare cells for CIN tolerance.…”
Section: The Paradox Of Aneuploidy In Tumorigenesismentioning
confidence: 99%
“…For instance, lymphocytes from individuals born with systemic and stable trisomies for either chromosome 13, 18 and 21 show an increased frequency of aneuploidies for three other autosomes (chromosomes 8, 15 and 16) compared to lymphocytes of healthy controls suggesting that stable aneuploid cells tend to destabilize their genomes [101]. Similarly, DLD1 colorectal cancer cells carrying an extra chromosome 7 or 13 display reduced mitotic fidelity compared to diploid DLD1 cells [30], further suggesting that aneuploidy can induce chromosome missegregation.…”
Section: Potential Aneuploidy-targeting Therapeutic Strategiesmentioning
confidence: 99%
“…Moreover, addition of a single chromosome in MEF cells induces a stress response that impairs proliferation and immortalization (Williams et al, 2008). However, numerical aneuploidy can lead to chromosomal instability (Nicholson et al, 2015) which results in subchromosomal gains and losses as observed in human tumors, in mouse models of cancer, and in immortalized MEF cells. Thus, aneuploidy can cause an initial fitness loss due to the costs of dealing with non-optimized chromosome numbers, gene copy numbers, and resulting proteomic imbalances.…”
Section: Chromosomal Instability and Aneuploidy-positive And Negative...mentioning
confidence: 99%
“…2b, white triangles). Most balanced diploid control cultures also gained CNAs over extended time , and structural variation (SV) [19][20][21] . Whole-genome duplication (WGD) occurs often during tumorigenesis and is associated with intra-tumoral heterogeneity [22][23][24][25][26] , therapeutic resistance and poorer outcomes [27][28][29] .…”
Section: In Vitro Evolution Recapitulates Arm-level Events In Tumorsmentioning
confidence: 99%
“…30,32,69 There are several key indicators of CIN, including lagging chromosomes, chromosome bridges, micronuclei, aneuploidy, and polyploidy. [70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86] As will be discussed below, aberrant spindle assembly checkpoint (SAC) activity, impaired sister chromatid segregation, aberrant centrosome number, and microtubule-kinetochore attachment error could lead to chromosome missegregation. This could in turn increase the formation of lagging chromosomes, which are chromosome that moves to the poles of the cell during cell division slower than other chromosomes, and chromosome bridges, which are structures formed when part of sister chromatids intertwines and fails to completely segregate.…”
Section: Causes Of Cinmentioning
confidence: 99%
“…The linear fit and regression value (R 2 ) are also shown in the graph. To calculate the fraction of ana-telophase cells with lagging chromosomes for each cell line, data from the Pellman ( Ganem et al, 2009 ), Compton ( Thompson and Compton, 2008 ), and Cimini ( Silkworth et al, 2009 ; Nicholson and Cimini, 2013 ; Nicholson et al, 2015 ) labs were averaged (if applicable). Centrosome amplification data for the cell lines are from Marteil et al ( Marteil et al, 2018 ) and Baudoin et al ( Baudoin et al, 2020 ).…”
Section: Extra Centrosomes Are Not Required For Tetraploid Cells To P...mentioning
confidence: 99%
“…When cells produce extra amounts of proteins, the fine balance in these tightly regulated processes can be disrupted, resulting in metabolic and replication stress. Furthermore, having extra copies of chromosomes can in itself affect mitosis, resulting in chromosomal instability and in further mitotic stress [85,90]. Also, specific aneuploidies differentially impair the post-implantation developmental potential of human embryos, resulting in diverse developmental fates [91].…”
Section: Consequences Of Decreased Mitotic Fidelity In Pluripotent St...mentioning
confidence: 99%
“…These strains have been used to uncover generic cellular responses to aneuploidy (Torres et al 2007 ; Pavelka et al 2010 ; Beach et al 2017 ; Ravichandran et al 2018 ). Subsequent analyses of human and mouse cell lines carrying specific trisomies or monosomies have revealed very similar effects on cell physiology as seen in yeast, including impaired cellular fitness and proliferative potential due to the proteotoxic, metabolic and replication stresses associated with chromosomal gains, or impaired ribosomal biogenesis linked to chromosomal losses (Williams et al 2008 ; Stingele et al 2012 ; Nicholson et al 2015 ; Meena et al 2015 ; Ohashi et al 2015 ; Santaguida et al 2015 ; Passerini et al 2016 ; Passerini et al 2016 ; Chunduri et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, trisomy of chr7 and chr13 conferred a growth advantage to colorectal cancer DLD-1 cells when cultured under challenging conditions such as hypoxia or low serum, although these aneuploid cells proliferated slower than their euploid counterparts in standard culture conditions (Rutledge et al 2016 ). Interestingly, trisomy 13, but not trisomy 7, was found to cause cytokinesis failure and elevated CIN in human colorectal cancer DLD-1 cells due to SPG20 overexpression (Nicholson et al 2015 ). Despite these significant findings, their clinical relevance and the molecular mechanisms by which these aneuploidies potentially drive cancer progression and metastasis require further investigation.…”
Section: Strategies To Introduce Specific Chromosomal Gainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments found that cells with a single chromosome addition often displayed more subsequent chromosome gains or losses [10]. Moreover, these cells displayed causes and/or characteristics of CIN, such as (ultrafine) anaphase bridges [10], micronuclei [11], chromosome mis-segregation and cytokinesis failure [12]. Aneuploidy in itself therefore also seems to be a possible ‘gateway’ to increasingly elevated CIN.…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches have been developed to model specific whole-chromosome and arm-level aneuploidies, including microcell-mediated chromosome transfer 20 , Cre-lox recombination of homologs to generate acentric and dicentric chromosomes 21 , CRISPR/Cas9-mediated arm-level and wholechromosome deletion 7,22 , and centromere inactivation of chromosome Y by inducible degradation of CENP-A 23 . Although these methods have generated valuable cell lines with particular chromosomal gains and losses 24,25 , all of these approaches rely on clonal expansion, and therefore cells may have evolved during cell culture following the initial karyotype change. Complementary to these targeted studies, others have assessed the short-term consequences of random karyotype changes in human cells predominantly after mitotic checkpoint inhibition [26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…Aneuploid mammalian and yeast cells exhibit proliferation defects (35) and genomic instability (69). In addition, cells harboring whole chromosome gains and losses display metabolic alterations (5,10) and experience proteotoxic stress, which is caused by aneuploidy-induced changes in protein abundance that place an increased demand on the cell’s protein folding and degradation machineries (3,4,1113).…”
Section: Introductionmentioning
confidence: 99%